Comparative analysis of heterogeneous gas-solid flow using dynamic cluster structure-dependent drag model in risers. (January 2020) - Xiaoxue, Jiang; Dan, Li; Shuyan, Wang; Hassan, M.; Wenjian, Cai; Weiqi, Chen; Huilin, Lu
Highlights: A drag energy dissipation minimization-based dynamic cluster structure-dependent drag model is proposed. A criterion of cluster existence is proposed to identify the heterogeneous flow and homogenous flow. The intermittency factor reveals the time fraction of cluster duration in the computational cells. Simulated cluster properties are compared with experimental results in risers. Abstract: An energy dissipation minimization-based dynamic cluster structure-dependent (DCSD) drag model is proposed using Euler-Euler two-fluid model (TFM) and kinetic theory of granular flow (KTGF). The DCSD drag model consists of a set of transient nonlinear equations which includes eight balance equations and one extreme value equation of the minimization of energy dissipation rate. The criterion of cluster existence is proposed to identify the heterogeneous flow and homogenous flow of gas-particles suspension. The intermittency factor is defined to describe the occurrence time of clusters. Three clustering mechanisms named collision-dominant (CD), collision-hydrodynamic-dominant (CHD) and hydrodynamic-dominant (HD) are identified as a result of the compromise in competition of energy dissipation rate components of hydrodynamic interactions and interactions of collision of particles. The CHD for particle clustering is the central mechanism, and CD is next in importance to HD. The predicted cluster diameter and solids volume fraction of clusters are compared to calculations using empirical correlations in literature. Graphical abstract: Image, graphical abstract The variation of controlling mechanism components of heterogeneous structures reveals that the clusters form as a result of the compromise in competition of hydrodynamic interactions and interactions of collision of particles in the riser.